Pre-attentive Mismatch Response and Involuntary Attention Switching to a Deviance in an Earlier-Than-Usual Auditory Stimulus: An ERP Study - Ungan, Pekcan; Karsilar, Hakan; Yagcioglu, Suha (Frontiers in Human Neuroscience, 2019)
An acoustic stimulus elicits an electroencephalographic response called auditory event-related potential (ERP). When some of the members of a stream of standard auditory stimuli are replaced randomly by a deviant stimulus and this stream is presented to a subject who ignores the stimuli, two different ERPs to deviant and standard stimuli are recorded. If the ERP to standard stimuli is subtracted from the ERP to deviant stimuli, the difference potential waveform typically exhibits a series of negative-positive-negative deflections called MMN, P3a, and RON, which are associated with pre-attentive change detection, involuntary attention switching, and reorienting of attention, respectively. The aim of the present study was to investigate how these pre-attentive processes are affected if the change occurs earlier than its usual timing implied by isochronous standard stimuli. In the MMN paradigm employed, 15% of the standards were randomly replaced by deviant stimuli which differed either in their pitch, or earlier onset time, or in both. Event-related responses to these three deviants [timely pitch change (RTP), earlier onset (REO), earlier pitch change (REP)] and to standards (RS) were recorded from 10 reading subjects. Waveforms of the “deviant-standard” difference potentials (DP) for “timely” and “early” pitch deviances were calculated as follows, respectively: DPTP = RTP–RS and DPEP = REP–REO. The MMN components of the DPs to timely and early pitch deviances had similar amplitudes, indicating that regularity of stimulus timing does not provide any benefit for the pre-attentive auditory change detection mechanism. Dynamics of the MMN and P3a components in scalp current density (SCD) maps suggested that an auditory change in a stimulus occurring earlier-than-usual initiates a faster and more effective call-for-attention and causes stronger attention switching than a timely change. SCD results also indicated that the temporal, frontal, and parietal MMN components are simultaneously present rather than emerging sequentially in time, suggesting a parallel deviance processing in the respective cortices. RONs to timely and early pitch deviances had similar amplitudes suggesting that the reorienting of attention that has been switched towards an early deviance is of the same strength with that switched towards a timely deviance.